Kajian Literatur: Aplikasi Metode Ekstraksi Modern Untuk Mengekstraksi Senyawa Fenolik dari Bahan Alam - Firdiyansyah, Moh. Rofiqi; Sindu Sakti, Aditya; Wulan Kusumo, Djati; Saiful Amin, Muhammad (Jurnal Farmasi (Journal of Pharmacy), 2024)
Phenolic compounds are phytochemicals obtained from plants as a response to stress. This compound has benefits as an antioxidant. Moreover, these compounds have an important role in preventing and treating several disorders such as atherosclerosis, brain dysfunction, diabetes mellitus, and cancer. Obtaining phenolic compounds from natural products, required an extraction method. A modern extraction method is an extraction process using several high technological instruments, to obtain high-yield extract in a short time. This review article performed to summarizes several modern extraction methods that can applied to extract phenolic compounds from natural products. The process of preparing this article was carried out comprehensively using various databases such as Google Scholar, Pubmed, Science Direct, Portal Garuda, NCBI, and BMC, using the keywords "Phenolic Compounds", "Microwave Assisted Extraction", "Enzyme Assisted Extraction", "High Hydrotastic Pressure Extraction”, “Ultrasonic Assisted Extraction”, “Pressure Liquid Extraction”, “Pressure Extraction Fluid”, and “Modern Extraction Methods”. The results show that the most optimal extraction method to extract total phenolics contents was using Microwave Assisted Extraction (MAE) method at 600 watts for 4 minutes using ethanol 70%, this procedure can produce 199.4 mgGAE/g total phenolics contents from the Pomegranate peel plant (Punica granatum L).